Conservative approach in localised rhabdomyosarcoma of the bladder and prostate: Results from International Society of Paediatric Oncology (SIOP) studies: Malignant mesenchymal tumour (MMT) 84, 89 and 95. Issue 2 (29th August 2013) - Jenney, Meriel; Oberlin, Odile; Audry, Georges; Stevens, Michael CG; Rey, Annie; Merks, Johannes HM; Kelsey, Anna; Gallego, Soledad; Haie‐Meder, Christine; Martelli, Hélène
Abstract Background The three sequential SIOP MMT studies provide the largest dataset available to date, to define the patient and tumour characteristics, treatment modalities and event‐free and overall survival for children with non metastatic rhabdomyosarcoma (RMS) of the bladder and/or prostate (BP). Procedure The combined dataset of 172 patients with BP RMS treated on the SIOP MMT 84, 89 and 95 studies was reviewed to determine tumour characteristics, details of treatment and outcome. Results Median age at diagnosis was 2.5 years (range 2 months–17.8 years) and 138 (79%) were males. Median follow‐up was 11.4 years (range 3 months–22 years). The 5‐year overall survival of the combined cohort was 77% (CI 70–83%). The 5‐year event‐free survival was 63% and included 7 patients (4%) who did not achieve complete remission (CR), and 57 (33%) who relapsed. Age ≥ 10 years (RR 3.7) and alveolar pathology (RR 3.3) were identified as independent prognostic factors on multivariate analysis. Fifty‐nine (50%) of the 119 survivors were cured without significant local therapy, improving from 31% in MMT84 study to 61% in MMT95 study. Conclusion The clinical strategy of the MMT studies aims to minimise the burden of therapy whilst maintaining survival rates. Overall survival is comparable to that of other international groups, despite the lower use of radiotherapy and or radical surgery, although number of events experienced is higher. Further assessment of the late effects of therapy is required to confirm whether this approach results in lower morbidity in the long‐term. Pediatr Blood Cancer 2014;61:217–222. © 2013 Wiley Periodicals, Inc.